Non-contact Pulse-based Radar with an Excited RF Pulse Generator for Vital-sign Application - Chen, Wei-Hsien; Chang, Chia-Hung; Kuo, Chien-Nan; Hsu, Chia-Chin (Progress in Electromagnetics Research Symposium, 2019)
This paper presents a pulse-based investigation to generate a serial of sensing pulses for probing the reciprocal movements of heartbeat and chest, respectively. An excited self-contained RF pulse generator with digital assisted controller is used for pulse shaping and performing nanosecond sensing pulses. In addition, the generator is implemented by a common source field-controlled transistor and a contour circuit by micro-strip line. Hence, in this paper, probing pulses and receives the echoes from the investigated subject back and forth by the whole sensing radar based on the monostatic antenna system. The demodulator is utilized to perform the multiplication of the reference probing waves and the return echoes delayed by the time interval between the emitted signal and reflected waves back to the radar module. The following analog baseband processing circuits with 3-stage topology for further amplifying and filtering the received physiological information help to increase the overall signal-to-noise ratio (SNR). The measured results demonstrate that the radiated RF pulses and vital signs are expected.